2020
DOI: 10.1111/jnc.15134
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine promotes the neurodegenerative potential of β‐synuclein

Abstract: A contribution of α‐Synuclein (α‐Syn) to etiology of Parkinson´s disease (PD) and Dementia with Lewy bodies (DLB) is currently undisputed, while the impact of the closely related β‐Synuclein (β‐Syn) on these disorders remains enigmatic. β‐Syn has long been considered to be an attenuator of the neurotoxic effects of α‐Syn, but in a rodent model of PD β‐Syn induced robust neurodegeneration in dopaminergic neurons of the substantia nigra. Given that dopaminergic nigral neurons are selectively vulnerable to neurod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 63 publications
(102 reference statements)
0
16
0
Order By: Relevance
“… 38 Some of these products can even interact with β‐synuclein and promote its aggregation. 39 Indeed, by regulating DA synthesis and storage, α‐synuclein might contribute to protect dopaminergic neurons from oxidation‐induced toxicity. The regulatory activities of α‐synuclein on synapse homeostasis might also be of great relevance in other neurotransmitter systems, which have been only partially examined, that is, other monoaminergic centers of the brain.…”
Section: Physiological Roles Of Synucleinsmentioning
confidence: 99%
“… 38 Some of these products can even interact with β‐synuclein and promote its aggregation. 39 Indeed, by regulating DA synthesis and storage, α‐synuclein might contribute to protect dopaminergic neurons from oxidation‐induced toxicity. The regulatory activities of α‐synuclein on synapse homeostasis might also be of great relevance in other neurotransmitter systems, which have been only partially examined, that is, other monoaminergic centers of the brain.…”
Section: Physiological Roles Of Synucleinsmentioning
confidence: 99%
“…Loss of dopaminergic neurons is a major pathological feature of Parkinson's disease, and therefore the experimental system that can study the characteristics of dopaminergic neurons is needed. In recent years, studies have started induced pluripotent stem cells (iPSCs) to differentiate into a dopaminergic neuron phenotype to generate human-derived dopaminergic neurons and have identified their susceptibility to toxicity [ 30 , 31 ]. Meanwhile, studies confirmed the presence of increased ROS accumulation and impaired autophagy in them [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed that ACR-induced locomotor abnormalities and neurotoxicity are comparable to the effects seen in PD, as ACR can cause key parkinsonian pathology such as αsynuclein aggregation [61]. The prominent hallmark of PD is the depletion of monoamine neurotransmitters (NTs) known as dopamine (DA) and its associated loss of dopaminergic A9 neurons in the substantia nigra pars compacta and striatum [58,62,63]. Motor control, cognitive decline, muscular stiffness, body posture instability, and movement difficulties are symptoms associated with the loss of dopaminergic A9 neurons [62].…”
Section: Acrylamide Induced Dopaminergic Neuronal Loss In Rat Striatummentioning
confidence: 99%
“…The prominent hallmark of PD is the depletion of monoamine neurotransmitters (NTs) known as dopamine (DA) and its associated loss of dopaminergic A9 neurons in the substantia nigra pars compacta and striatum [58,62,63]. Motor control, cognitive decline, muscular stiffness, body posture instability, and movement difficulties are symptoms associated with the loss of dopaminergic A9 neurons [62]. DA, a kind of catecholamine, is a NT that governs important functions like cognition, motor control, emotion, and neuroendocrine activity [1,7,63].…”
Section: Acrylamide Induced Dopaminergic Neuronal Loss In Rat Striatummentioning
confidence: 99%